Extent of Adoption of Castor Production Technology by FLD and Non- FLD Farmers in Banaskantha District of Gujarat State - Kakkad, DM; Patel, GR; Thakur, NB (Indian Journal of Extension Education, 2021)
The study was conducted in three talukas (Dantiwada, Vadgam, and Dhanera) of Banaskantha District. All nine villages in which frontline demonstrations on castor crop were conducted by KVK, Deesa, were selected and a total of 150 respondents were selected for the study. The result revealed that nearly three-fifths (57.33%) of FLD respondents were in the medium randomly category of adoption of castor production technology. WhereasÂ 22.67 per cent had high and 20.00 per cent had low extent of adoption. In case of Non-FLD farmers, the majority had the medium extent of adoption of castor production technology, whereas 30.67 per cent had low and 13.33 per cent had a high level of adoption.